2021
DOI: 10.5812/archcid.118243
|View full text |Cite
|
Sign up to set email alerts
|

Development of Multi-epitope Subunit Vaccine Against Pseudomonas aeruginosa Using OprF/OprI and PopB Proteins

Abstract: Background: The emerging problem of antibiotic resistance in Pseudomonas aeruginosa is a global health concern; hence, revealing innovative therapeutic approaches (such as designing an immunogenic vaccine candidate) is needed. There is no evidence of the availability of an effective vaccine that can combat the infection caused by this microorganism. Objectives: This research was conducted to develop a potential chimeric vaccine against P. aeruginosa using reverse vaccinology approaches. Methods: The present va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…It was also nontoxic and highly soluble. Overall, it might stimulate the immune system and suppress P. aeruginosa [208]. Dey et al (2022) demonstrated that the primary membrane protein candidate of P. aeruginosa was a crucial factor in the susceptibility of the bacteria to antimicrobial peptides and its ability to survive inside hosts [209].…”
Section: (B Cell Responses Are Classified As T-dependent (T-d) or T-i...mentioning
confidence: 99%
See 2 more Smart Citations
“…It was also nontoxic and highly soluble. Overall, it might stimulate the immune system and suppress P. aeruginosa [208]. Dey et al (2022) demonstrated that the primary membrane protein candidate of P. aeruginosa was a crucial factor in the susceptibility of the bacteria to antimicrobial peptides and its ability to survive inside hosts [209].…”
Section: (B Cell Responses Are Classified As T-dependent (T-d) or T-i...mentioning
confidence: 99%
“…Reverse vaccinology techniques were employed in an experimental study to develop a potent chimeric vaccine against P. aeruginosa [ 208 ]. The vaccine candidate included PopB and outer membrane protein F and I (OprF/OprI) joined together using linkers.…”
Section: From Research To Real-world Experience: Currently Approved A...mentioning
confidence: 99%
See 1 more Smart Citation